Catalyst for producing synthesis gas by electrically reducing CO2 as well as preparation method and application of catalyst
Through the precipitation method of M-ZnO catalyst, the problems of complex catalyst preparation and small synthesis gas ratio in the prior art are solved, and the synthesis gas ratio is widely adjusted and the adaptability of industrial applications is achieved.
Patent Information
- Application Number
- CN202510104000.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-23
AI Technical Summary
The existing electroreduced CO2 catalyst preparation method is complex, and the synthesis gas ratio range is small, so it cannot accurately adapt to the production of downstream chemicals.
The M-ZnO catalyst is used to synthesize through the precipitation method, and the metal doping amount and external potential are adjusted to the synthesis gas ratio. The preparation method is simple and suitable for large-scale synthesis.
It has achieved extensive adjustment of the synthesis gas ratio, meets the industrial production needs of fermentation, Fischer Tropsch synthesis, etc., and the reaction process is safe and non-toxic, and is suitable for large-scale applications.
Smart Images

Figure CN119913560A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of CO / H2 synthesis gas preparation, and relates to a catalyst for preparing synthesis gas by electro-reduction of CO2 and a preparation method thereof. Background Art
[0002] With the rapid development of China's economy and the acceleration of industrialization, the consumption of fossil fuels has increased dramatically. The concentration of CO2 in the atmosphere has increased significantly in the past 20 years and is currently close to 420ppm, with an annual growth rate of 0.5%. The global average temperature has also risen by 0.5℃ between 2001 and 2024. In order to better cope with the major global challenge of global climate change, CO2 emissions can be controlled and minimized through electrocatalysis, photocatalysis, thermal catalysis and other methods to convert them into various valuable compounds. The electrocatalytic method can not only realize the resource utilization of CO2 and promote the better completion of the carbon cycle, but also effectively utilize renewable energy. It is regarded as one of the most promising CO2 conversion and utilization technologies in the 21st century.
[0003] Electrocatalysis is a very promising CO2 utilization strategy that can directly convert CO2 into high value-added chemicals and fuels under mild reaction conditions. In particular, the product CO and the byproduct H2 can be combined in the reaction medium of water through the electrocatalytic CO2 reduction reaction (CO2RR) to produce synthesis gas (CO / H2). Synthesis gas with different CO and H2 molar ratios can be precisely adapted to downstream chemical processes for the production of different chemicals. For example, the CO / H2 ratio required for synthesis gas fermentation is 1 to 3.3; the CO / H2 ratio required for Fischer-Tropsch synthesis is 0.4 to 2.0; the CO / H2 ratio required for alcohol production is 0.5 to 1.0; the CO / H2 ratio required for methanol production is 1.0; and the CO / H2 ratio required for methanation of synthesis gas is 0.3. Mitra Bagheri et al. used a green steam-assisted dry gel method to synthesize porous ZIF-8 and ZIF-67 catalysts for the electroreduction of CO2. By controlling the morphology of the catalyst, synthesis gas with an adjustable CO / H2 ratio was produced. However, the preparation method of metal organic framework (MOFs) catalysts is relatively cumbersome. The maximum CO / H2 ratio produced within the test range is only about 2.0, and the ZIF-8 catalyst produces 10-15% formate by-products under the test conditions, which is not suitable for large-scale industrial applications (ChemSusChem, 2024: e202400684.). Mao et al. prepared Cu2O / In(OH)3 with a heterojunction structure as an electrocatalyst for producing synthesis gas. Within the voltage range of -0.665V to -1.235V (vs.RHE), by adjusting the Cu / In feed ratio, the synthesis gas ratio can be adjusted from 1:2 to 1:1, and it shows high stability. However, the synthesis gas ratio range is small, which limits the production of diverse chemicals (Applied Surface Science.2024,160114). Summary of the invention
[0004] The purpose of the present invention is to solve the problems that the existing electro-reduction of CO2 to produce synthesis gas (CO / H2) catalyst preparation method is complicated, the synthesis gas ratio range is small, and it is not possible to accurately adapt to the production of downstream chemicals. A catalyst for preparing synthesis gas by electro-catalytic CO2 reduction reaction (CO2RR) and its preparation method are provided. The synthesized M-ZnO catalyst not only has good performance of preparing synthesis gas by CO2RR, but also has a simple catalyst preparation method, and the entire reaction process is safe and non-toxic, which is suitable for large-scale synthesis.
[0005] The technical solution of the present invention:
[0006] A catalyst for electroreduction of CO2 to produce synthesis gas, having a general chemical formula of M-ZnO, wherein M is one or a mixture of two or more metal elements such as gallium (Ga), cerium (Ce), lanthanum (La), zirconium (Zr), iron (Fe), nickel (Ni), palladium (Pd), rhodium (Rh), platinum (Pt), etc.
[0007] A method for preparing a catalyst for electroreduction of CO2 to produce synthesis gas, comprising the following steps:
[0008] Step 1, dissolving the metal source in alcohol and mixing by ultrasonication to form a uniform precursor solution;
[0009] Step 2, slowly adding the precipitant to the precursor solution, heating and stirring, standing, and centrifuging to obtain a solid precipitate;
[0010] Step 3: Wash the solid precipitate and vacuum dry it. After fully grinding, put it into a muffle furnace for heating and calcining. After completion, naturally cool it to room temperature. After fully grinding, obtain the M-ZnO catalyst.
[0011] It is further defined that the metal source in step 1 includes two parts: a Zn source and a doped metal source. The Zn source is one or a mixture of two or more of a variety of Zn-containing compounds such as zinc nitrate and zinc chloride; the doped metal source is one or a mixture of two or more of a variety of compounds containing the metal element such as nitrate and chloride, wherein the molar ratio of the doped metal element to the total amount of metal (M / (M+Zn)) is in the range of 0.1 to 30%.
[0012] It is further defined that the doped metal source includes but is not limited to one or a mixture of two or more of the following metal elements: gallium (Ga), cerium (Ce), lanthanum (La), zirconium (Zr), iron (Fe), nickel (Ni), palladium (Pd), rhodium (Rh), platinum (Pt), etc.
[0013] Further defined, the alcohol in step 1 includes commonly used alcohol solvents such as ethanol, isopropanol, n-butanol, ethylene glycol, n-hexanol, etc., preferably ethanol. The ratio of the metal source to the alcohol is (0.01-5) g: (150-250) mL.
[0014] Further limited, the precipitant in step 2 can be selected from a variety of precipitants such as oxalic acid, ammonia water, urea, etc. Among them, when a liquid precipitant (such as oxalic acid, ammonia water, etc.) is selected, the volume ratio of the precipitant to the precursor solution in step 1 is 1:1 to 1:5, preferably 1:2.5; when a solid precipitant (such as urea, etc.) is selected, the molar ratio of the precipitant to the total amount of the metal element in step 1 is 1:1 to 3:1.
[0015] It is further defined that in step 2, stirring is performed by heating in a water bath or an oil bath, the reaction is performed at a temperature of 30 to 130° C., preferably 70° C., and the stirring time is 0.3 to 3 h, preferably 1 h.
[0016] It is further defined that the solid precipitate in step 3 needs to be washed with alcohol at least once and with deionized water at least once.
[0017] It is further defined that the drying temperature in step 3 is 30 to 100° C., preferably 80° C., and the drying time is 1 to 48 hours.
[0018] It is further defined that the calcination temperature in step 3 is 400-600° C., preferably 600° C., and the heating time is 3-5 hours, preferably 4 hours.
[0019] A method for preparing an M-ZnO electrode, the preparation method is carried out according to the following steps:
[0020] The M-ZnO catalyst was dissolved in a mixed solution of alcohol and Nafion, and was evenly coated on the surface of carbon paper after ultrasonic treatment. The M-ZnO electrode was obtained after drying.
[0021] It is further defined that the loading amount of the M-ZnO catalyst is 1 to 4 mg / cm 2 , preferably 2 mg / cm 2 .
[0022] To further define, alcohol includes commonly used volatile alcohol solvents such as ethanol and isopropanol, preferably ethanol.
[0023] It is further defined that the volume ratio of the alcohol to the Nafion solution is (80-120):1, preferably 100:1.
[0024] The application of an M-ZnO electrode in preparing synthesis gas (CO / H2) is carried out according to the following steps:
[0025] Step 1: Use M-ZnO electrode as working electrode, Ag / AgCl as reference electrode, Pt electrode as counter electrode, add electrolyte, and assemble the electrolytic cell device.
[0026] Step 2: CO2 is continuously introduced into the electrolyte at a constant rate to perform constant potential electrolysis to obtain synthesis gas in a suitable industrial synthesis ratio range.
[0027] It is further defined that the electrolyte in step 1 may include one or a mixture of two or more of KHCO3, KCl, etc., with a concentration of 0.05 to 1.0 M and a volume of 40 to 70 mL.
[0028] It is further defined that the electrolytic cell device in step 1 includes an H-type electrolytic cell, a flow-type electrolytic cell, a membrane electrolytic cell, and the like.
[0029] It is further defined that the flow rate of CO2 introduced into the electrolytic cell device is 5 to 50 mL / min, preferably 20 mL / min.
[0030] Beneficial effects of the present invention:
[0031] (1) The M-ZnO catalyst is synthesized by precipitation method. The synthesis method is simple, the reaction conditions are mild, and it is suitable for large-scale synthesis. The obtained catalyst is in powder form, stable in nature, and easy to store.
[0032] (2) The M-ZnO catalyst prepared by the present invention can reduce CO2 to synthesis gas through CO2RR, and the synthesis gas ratio can be adjusted by the metal doping amount and the external potential. The obtained synthesis gas meets the vast majority of industrial production needs such as fermentation and Fischer-Tropsch synthesis.
[0033] (3) From a microscopic perspective, the present invention constructs a series of M-ZnO catalysts with rich defect structures and uses them to prepare syngas with adjustable ratios in CO2RR. The entire reaction process is safe and non-toxic. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 X-ray diffraction patterns of 2% Ga-ZnO, 5% Ga-ZnO, 10% Ga-ZnO, 15% Ga-ZnO, and ZnO catalysts in Examples 1 to 4 and Comparative Example 1;
[0035] Figure 2 EPMA graph and corresponding EDS element distribution graph of the 5% Ga-ZnO catalyst in Example 2; wherein, (a) is the EPMA graph of the 5% Ga-ZnO catalyst, (b) is the distribution of the Zn element in the 5% Ga-ZnO catalyst, (c) is the distribution of the Ga element in the 5% Ga-ZnO catalyst, (d) is the distribution of the O element in the 5% Ga-ZnO catalyst, and (e) is the distribution of the Zn, Ga, and O elements in the 5% Ga-ZnO catalyst;
[0036] Figure 3 The stability test results of the 5% Ga-ZnO catalyst prepared in Example 2, wherein (a) is the Faraday efficiency and ratio change of the synthesis gas product, and (b) is the current density change in the entire test range. DETAILED DESCRIPTION
[0037] The specific implementation of the present invention is further described below in conjunction with the technical scheme and the accompanying drawings.
[0038] The Zn-based catalyst described in the present invention is a catalyst synthesized by a precipitation method. Here, the Zn-based catalyst prepared by using oxalic acid as a precipitant is introduced as an example.
[0039] The raw materials were weighed according to the molar ratio of metal source to zinc source of 1:9, mixed and dissolved in ethanol, and ultrasonicated at room temperature to form a precursor solution. Excess oxalic acid solution was added dropwise to the above precursor solution as a precipitant and mixed and stirred, and stirred continuously for 1 hour in a 70°C water bath, and then aged at room temperature for 2 hours. The mixed solution was then centrifuged and washed alternately with ethanol and deionized water, and the obtained white solid precipitate was dried at 80°C for 12 hours, fully ground, and calcined at 600°C in a muffle furnace for 4 hours to obtain a catalyst.
[0040] The structure of the Zn-based catalyst can be optimized by changing the type and ratio of the metal source, zinc source, precipitant and synthesis conditions in the raw materials. The synthesis of some metal-doped Zn-based catalysts is shown in Table 1.
[0041] Table 1. Preparation of metal-doped Zn-based catalysts
[0042]
[0043]
[0044] ZnO without metal doping was selected as a comparative example, and its preparation process was the same as above, except that only zinc source was added as the metal source without other metal sources.
[0045] According to the catalyst synthesized in the above table, prepare the electrode for producing synthesis gas. Specifically, follow the following steps:
[0046] 2 mL of ethanol and 20 μL of 5% Nafion solution were ultrasonically mixed and then 2 mg of catalyst powder was added. The mixture was then ultrasonically treated and then evenly coated on carbon paper (1×1 cm 2 ). After drying for 30 min, the M-ZnO electrode was obtained.
[0047] Application of the prepared M-ZnO electrode in the preparation of CO / H2 synthesis gas:
[0048] (1) Take 55 mL of 0.1 M KHCO3 solution as the cathode electrolyte.
[0049] (2) Take 55 mL of 0.1 M KHCO3 solution as the anolyte.
[0050] (3) An H-type double-chamber electrolytic cell was assembled using an M-ZnO electrode as a cathode working electrode, an Ag / AgCl electrode as a reference electrode, and a Pt electrode as a counter electrode, wherein the cathode and anode chambers were separated by a proton exchange membrane.
[0051] (4) High-purity CO2 gas was continuously and stably introduced into the cathode chamber and the anode chamber at a flow rate of 20 mL / min for 30 minutes to remove the remaining impurity gases in the device. Then, voltages of -0.79 V to -1.29 V (vs. RHE) were applied in sequence to test the performance of electroreduction of CO2, where each catalyst was pretreated at -0.69 V (vs. RHE) for 30 minutes before the formal test. The electrochemical performance of the catalyst was tested and analyzed using a CHI630E electrochemical workstation, and the gas phase products were directly sampled from the sealed electrolysis system and then subjected to gas chromatography testing, where CO was detected by a hydrogen flame ionization detector (FID) and H2 was detected by a thermal conductivity detector (TCD). The gas chromatography test results were used to qualitatively and quantitatively analyze the products and their Faraday efficiency.
[0052] For the electrocatalytic reaction examples of different catalysts, electrodes were prepared according to the above method for the catalysts of Examples 1 to 8. Table 2 lists the specific applications of Examples 1 to 8 and their effect data.
[0053] Table 2. Specific applications of some catalysts and their effect data
[0054]
[0055] The Faraday efficiency of the gas phase products obtained by electrolysis in the above-mentioned examples and comparative examples within the potential range of -0.79 to -1.29 V (vs. RHE) was measured.
[0056] For the 2% Ga-ZnO catalyst of Example 1, its Faraday efficiency of CO can reach up to 58.56%, the total Faraday efficiency of synthesis gas is close to 90%, and the Faraday efficiency ratio of CO and H2 in the synthesis gas (CO / H2) is in the range of 0.27 to 1.90, which is a good synthesis gas ratio and is suitable for the industrial production of alcohol chemicals such as methane and methanol.
[0057] For the 5% Ga-ZnO catalyst of Example 2, its Faraday efficiency of CO can reach up to 64.59%, the total Faraday efficiency of synthesis gas is close to 90%, and the Faraday efficiency ratio of CO and H2 in the synthesis gas (CO / H2) is in the range of 0.21 to 3.07, which is a good synthesis gas ratio and is suitable for synthesis gas fermentation.
[0058] For the 10% Ga-ZnO catalyst of Example 3, its Faraday efficiency of CO can reach up to 70.66%, the total Faraday efficiency of synthesis gas is close to 90%, and the Faraday efficiency ratio of CO and H2 in the synthesis gas (CO / H2) is in the range of 0.30 to 3.98, which is a good synthesis gas ratio and is suitable for Fischer-Tropsch synthesis of various high value-added hydrocarbon chemicals.
[0059] For the 15% Ga-ZnO catalyst of Example 4, its Faraday efficiency of CO can reach up to 69.19%, the total Faraday efficiency of synthesis gas is close to 90%, and the Faraday efficiency ratio of CO and H2 in the synthesis gas (CO / H2) is in the range of 0.27 to 3.64, which is a good synthesis gas ratio and is suitable for Fischer-Tropsch synthesis of various high value-added alcohol chemicals.
[0060] For Examples 5-8, by changing the type and ratio of the doped metal elements, a wide range of changes in the synthesis gas ratio can be achieved, which can be accurately adapted to the industrial production of a variety of downstream chemicals.
[0061] For the ZnO catalyst of Comparative Example 1, the maximum Faraday efficiency of CO is only 49.87%, and the maximum total Faraday efficiency of synthesis gas is only 82.84%, which will be greatly reduced with the increase of the applied potential, indicating that a large amount of by-products are generated during the reaction, which not only reduces the purity of the synthesis gas, but also increases the complexity and cost of the subsequent separation and purification steps. In addition, the Faraday efficiency ratio of CO and H2 in the synthesis gas (CO / H2) is in the range of 0.63 to 1.25, which is a small ratio range, limiting the industrial production potential of synthesis gas.
[0062] Characterization test and analysis were performed on some embodiments.
[0063] The 2% Ga-ZnO, 5% Ga-ZnO, 10% Ga-ZnO, 15% Ga-ZnO, and ZnO catalysts obtained in the first step of Examples 1 to 4 and Comparative Example 1 were tested by X-ray diffraction. The test results are as follows: Figure 1 The five synthesized catalysts can correspond to the main peak of ZnO in the standard PDF card (PDF#36-1451). At the same time, Ga does not show obvious diffraction peaks because it is highly dispersed on the ZnO surface.
[0064] The EPMA image of the 5% Ga-ZnO catalyst obtained in Example 2 was analyzed by energy dispersive X-ray spectroscopy (EDS), as shown in FIG. Figure 2 As shown in Figure 2, the material is composed of Zn, Ga and O elements, each of which is evenly distributed and highly dispersed on the ZnO surface.
[0065] The electrocatalytic reduction test of the system in Example 2 was tested for stability to determine the stability of the synthesized 5% Ga-ZnO catalyst. Figure 3 As shown, in the long-term stability test, the current density and the CO / H2 synthesis gas ratio remained basically stable, indicating that the catalyst has good electrochemical stability, is not easy to deactivate, and is expected to be promoted for industrial application.
[0066] In summary, compared with the existing material preparation method for preparing synthesis gas by electrocatalytic reduction of CO2, the present invention has the following advantages: it has good performance of preparing synthesis gas by CO2RR, and the catalyst synthesis method is simple, the whole reaction process is safe and non-toxic, and it is suitable for large-scale synthesis. The present invention can adjust the proportion of synthesis gas by adjusting the doping amount of metal and the applied potential, which is conducive to the wide application of CO2RR synthesis gas preparation technology.
[0067] The preferred embodiments of the present invention have been described in detail above, but the present invention is not limited to the embodiments described herein. Many equivalent substitutions and modifications made without departing from the spirit and principle of the present invention should be included in the scope of the present invention.
Claims
1. A catalyst for electroreduction of CO2 to produce synthesis gas, characterized in that: The general chemical formula of the catalyst is M-ZnO, wherein M is one or a mixture of two or more of Ga, Ce, La, Zr, Fe, Ni, Pd, Rh and Pt.
2. A method for preparing the catalyst according to claim 1, characterized in that: Here are the steps: Step 1, dissolving the metal source in alcohol and mixing by ultrasonication to form a uniform precursor solution; Step 2, slowly adding the precipitant to the precursor solution, heating and stirring, standing, and centrifuging to obtain a solid precipitate; Step 3: Wash the solid precipitate and vacuum dry it. After fully grinding, put it into a muffle furnace for heating and calcining. After completion, naturally cool it to room temperature. After fully grinding, obtain the M-ZnO catalyst.
3. The preparation method according to claim 1, characterized in that: In step 1, The metal source includes two parts: a Zn source and a doped metal source, wherein the molar ratio of the doped metal source to the metal source is 0.1 to 30%; wherein the Zn source is zinc nitrate and / or zinc chloride; and the doped metal source is one or a mixture of two or more of nitrate and chloride; The alcohol includes ethanol, isopropanol, n-butanol, ethylene glycol, and n-hexanol, and the ratio of the metal source to the alcohol is 0.01-5 g: 150-250 mL.
4. The preparation method according to claim 1, characterized in that: In step 2, The precipitant is selected from oxalic acid, ammonia water, and urea; wherein, when a liquid precipitant is selected, the volume ratio of the precipitant to the precursor solution is 1:1 to 1:5; when a solid precipitant is selected, the molar ratio of the precipitant to the total amount of the metal element in step 1 is 1:1 to 3:1; The mixture is stirred by heating in a water bath or an oil bath, and the reaction is carried out at a temperature of 30 to 130° C. The stirring time is 0.3 to 3 hours.
5. The preparation method according to claim 1, characterized in that: In step 3, The solid precipitate needs to be washed with alcohol at least once and with deionized water at least once; The drying temperature is 30-100°C and the drying time is 1-48h; The calcination temperature is 400-600°C, and the calcination time is 3-5h.
6. A method for preparing an M-ZnO electrode using the catalyst according to claim 1, characterized in that: Follow these steps: The M-ZnO catalyst was dissolved in a mixed solution of alcohol and Nafion, and was evenly coated on the surface of carbon paper after ultrasonic treatment. The M-ZnO electrode was obtained after drying.
7. The method according to claim 6, characterized in that The loading amount of M-ZnO catalyst is 1~4mg / cm 2 ; Alcohols include ethanol and isopropanol; The volume ratio of alcohol to Nafion solution is (80-120):
1.
8. Use of the M-ZnO electrode prepared by the method according to claim 6 in preparing synthesis gas, characterized in that: Follow these steps: Step 1: Using M-ZnO electrode as working electrode, Ag / AgCl as reference electrode, Pt electrode as counter electrode, adding electrolyte, and assembling electrolytic cell device; Step 2: CO2 is continuously introduced into the electrolyte at a constant rate to perform constant potential electrolysis to obtain synthesis gas in a suitable industrial synthesis ratio range.
9. The use according to claim 8, characterized in that: The electrolyte is KHCO3 and / or KCl with a concentration of 0.05 to 1.0 M; The electrolytic cell device is an H-type electrolytic cell, a flow-type electrolytic cell or a membrane electrolytic cell; The flow rate of CO2 introduced into the electrolytic cell device is 5 to 50 mL / min.
Citation Information
Patent Citations
Catalyst, preparation method and application thereof
CN112774724A
Preparation method of doped ZnO catalyst and preparation method for synthesizing higher alcohol by using catalyst
CN113856687A
Preparation method and application of diatomic catalyst with M1M2-carrier structure
CN115704097A
Mg-Ni bimetallic monatomic catalyst for preparing proportion-adjustable synthesis gas through electro-catalysis carbon dioxide reduction and preparation method and application of Mg-Ni bimetallic monatomic catalyst
CN117822033A
PREPARATION METHOD OF DOPED ZnO CATALYST AND SYNTHESIS METHOD OF HIGHER ALCOHOL USING SAME
US20230138719A1